Biography of João Carlos Teixeira Brandão: from alienist to director of the 1st Brazilian School of Nursing - Junior, Marcos Vinicio Araujo; Moreira, Almerinda; Rocha, Bruno (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2009)
This is the Biography of João Carlos Teixeira Brandão, the first director of the School of Professional Nurses, the first Brazilian school, today called Alfredo Pinto School of Nursing. The facts reported here were taken from the reports of the Care Service for the Alienated and a ministerial report issued in 1890, which were the primary sources used in the study, besides notes published in journals of the time, particularly the Jornal do Comércio. The content offers a social-political overview of the conditions in which a new labor class was constituted, i.e. nursing, and in which changes occurred for the alienated in Brazil.